ANALISIS PERAN ORANG TUA DALAM MELAKUKAN PENDAMPINGAN BELAJAR SISWA KELAS IV PADA MASA PANDEMI COVID-19 DI MI AL AMIN DESA SUMBERSARI KECAMATAN SRONO - Luluk Maktumah; Zidniyati Zidniyati; Khoirul Anwar (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2022)
This study has two purposes: 1.) explaining the role of parents in assisting students in grade IV students during the Covid-19 Pandemic, 2.) explain what factors hinder the role of parents in assisting students in class IV students during the covid-19 Pandemic. The type of research used is qualitative descriptive. The subjects in the study were parents and grade IV students totaling 26. The data collection techniques used in this study are observation, interview and questionnaire. The data analysis technique used in this study is miles and huberman data analysis consisting of data reduction, data display, and conclusion draw. The data validity technique in this study used triangulation techniques. The results of this study showed that there are 42% of parents involved in their child's learning assistance. Parents who are involved in learning their children on average have the ability to understand and explain the subject matter to children. In addition, they are able to motivate their children to continue their learning spirit. While there are as many as 58% of parents are less involved in accompanying their children to learn. Parents' inability to understand the subject matter and parents' difficulty in cultivating children's learning interests, are the main factors that cause parental involvement in accompanying their children's learning to be lacking.